Disneyization of drug use : understanding atypical intoxication in party zones - Turner, Tim, 1970- (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Disneyization of Drug Use offers an innovative, ground-up understanding of the atypical patterns of illegal drug use that often permeate multi-day party zones such as nightlife tourist resorts and music festivals. Drawing on ethnographic research conducted over three summers in Ibiza, the book contextualizes the drug and alcohol-related experiences of tourists and seasonal workers operating in the island's infamously hedonistic party spaces. Through an innovative application of Alan Bryman's (2004) seminal work, The Disneyization of Society, the book argues how the same marketing principles that generate consumption in the legal economy of Disney theme parks, also drives illicit drug use in Ibiza and music festivals, where the line between legal and illegal substances rapidly blurs to the point of collapse. This highly innovative book offers rich insights into the complex interplay between drug and alcohol use, agency, pleasure, risk, consumerism, and social context. It will be of great appeal to academics and students interested in the fields of cultural criminology, deviant leisure, drug and alcohol studies, youth culture, and ethnographic research methods"--
OCLC-licensed vendor bibliographic record.
Keywords: Music festival attendees -- Drug use; Parties; Drug traffic -- Social aspects; SOCIAL SCIENCE / Sociology / General; SOCIAL SCIENCE / Popular Culture; SOCIAL SCIENCE / Anthropology / Cultural